Explaining Presupposition Triggers - Zeevat, Henk (Proceedings of the Amsterdam Colloquium, 1999)
The paper proposes three revisions to the standard views of presupposition: the employment of optimality theory for the defaults and preferences, the admission of weak antecedents for presupposition resolution/satisfaction and fine-grained classification of presupposition triggers, based on the availability of expression alternatives and the logical requirement of the presupposition. The treatment is able of dealing with a range of phenomena that are outside the scope of any current presupposition theory.